STUDENT MANAGEMENT AT ISLAMIC STATE JUNIOR HIGH SCHOOL COT GUE ACEH BESAR - Fadhilah; Arisnaini; Eka Mayasari; Muliana (ITB AAS Indonesia Surakarta, 2026)
The application of students to institutional management is one of the needs to improve the quality of education. The lack of school facilities and infrastructure is the main obstacle in effective student management. This research aims to determine the planning, implementation, monitoring, and evaluation of student management programs. The method used in this study is a descriptive qualitative approach. Data collection techniques: observation, interviews and documentation. The subjects are the principal, teachers and students of MTsN Cot Gue. The results of the study show that: the student management plan prepared by the principal with the vice head of students and vice head of curriculum includes Admission courses, new student capacity, and the new student selection process, analyzing subjects, compiling annual programs, semester programs, syllabus and Learning Program Plans. All plans are drafted, drafted and documented. The implementation is adjusted to the student management plan prepared, both in relation to new admissions and student activities. Supervision of student management based on a management system, namely looking for every activity that has been planned, carried out and well supervised. Principals and teachers to supervise the implementation of student management. Both the principal and the teacher carry out roles and responsibilities based on the duties and functions for the management of student success. Activities and aspects of student assessment management based on the plan prepared. Evaluations are carried out to see the success and improve the activities that have been carried out.